Distribution of surface oxygen complexes on activated carbons from immersion calorimetry, titration and temperature-programmed desorption techniques - Stoeckli, Fritz; Moreno-Castilla, C.; Carrasco-Marín, Francisco; López-Ramón, M. V. (My University, 2002)
A. activated carbons; C. microcalorimetry, temperature-programmed desorption; D. immersion enthalpy, surface oxygen complexes